External and internal intensity profiles of older male and female participants during a walking football game. - Júlio A Costa; Catarina Pereira; Ana Barbosa; André Seabra; João Brito; Ana Pinto; Catarina Martins; Rafaela Moreira; Bruno Gonçalves (PLoS ONE)
Background Walking football (WF) can be used as an impactful activity for healthy aging and decrease the high levels of sedentary behavior among older adults. This study examines the external and internal intensity profiles of male and female participants during a WF tournament, addressing a gap in research on game demands and induced load. Methods The study involved 176 players aged 50 + participating in a 40-min, 5v5 WF tournament with unlimited substitutions. External intensity profiles (total and categorized distances) were measured using Global Positioning System (GPS), while heart rate (HR) monitors assessed internal intensity profiles, including absolute HR and intensity zones based on %HRmax. Results The proportion of male participants (n = 123; 70.3%) was higher than females (n = 52; 29.7%), p < .001. They were similar in age (61.6 ± 8.6 and 60.8 ± 6.9, respectively). Males covered a higher distance per minute than females, with sex showing a moderate effect (63.3 ± 10.7 m/min vs. 54.7 ± 15.8 m/min; p < .001; Cohen's dunbiased = 0.69 [0.36; 1.03]), especially in fast walking (41.7 ± 12.2 m/min vs. 32.6 ± 16.7 m/min; p < .001; Cohen's dunbiased = 0.66 [0.33; 1.00]). Males played more time than females (22:26 ± 09:47 min:ss vs. 15:41 ± 07:46 min:ss; p < .001), with moderate effect (Cohen's dunbiased = 0.73 [0.40; 1.06]). However, no differences between sexes were identified in the intensity load variables, such that the female average %HRmax was 80 ± 11% and the male was 82 ± 8% during the practice. Conclusions Overall, while males generally exhibit higher external intensity profiles in WF, both sexes experience similar internal intensity profiles, highlighting WF's potential as a scalable, health-promoting intervention for aging populations.